2004
DOI: 10.1128/aac.48.2.596-601.2004
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR Amplimer Conformation Analysis for Rapid Detection of gyrA Mutations in Fluoroquinolone-Resistant Mycobacterium tuberculosis Clinical Isolates

Abstract: A new strategy known as multiplex PCR amplimer conformation was developed for detection of mutation in the gyrA gene of 138 clinical isolates of Mycobacterium tuberculosis. The method generated a single-stranded and heteroduplex DNA banding pattern of multiplex PCR amplimers of the region of interest that was extremely sensitive to specific mutations, thus enabling much more sensitive and reliable mutation analysis compared to the standard single-stranded conformation polymorphism technique. The genetic profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 35 publications
7
91
0
2
Order By: Relevance
“…Some studies have reported that M. tuberculosis strains containing D94G mutation in the gyrA gene exhibit high-level resistance to FQs while those with D94A mutation have lower MIC for LFX [93,96,97]. On the contrary, other reports have not found an association of different mutation patterns in gyrA or gyrB genes with the level of FQ resistance in M. tuberculosis isolates [89,94]. Several genotypic tests have recently been developed (Table III) for rapid (within 1-2 days) detection of vast majority of FQ-resistant clinical M. tuberculosis isolates [95].…”
Section: Mechanism Of Action and Resistance Of Fluoroquinolones In Mmentioning
confidence: 72%
See 2 more Smart Citations
“…Some studies have reported that M. tuberculosis strains containing D94G mutation in the gyrA gene exhibit high-level resistance to FQs while those with D94A mutation have lower MIC for LFX [93,96,97]. On the contrary, other reports have not found an association of different mutation patterns in gyrA or gyrB genes with the level of FQ resistance in M. tuberculosis isolates [89,94]. Several genotypic tests have recently been developed (Table III) for rapid (within 1-2 days) detection of vast majority of FQ-resistant clinical M. tuberculosis isolates [95].…”
Section: Mechanism Of Action and Resistance Of Fluoroquinolones In Mmentioning
confidence: 72%
“…The presence of missense mutations in the so-called quinolone resistance-determining region (QRDR) of gyrA or gyrB genes conferring resistance to FQs was subsequently confirmed by using clinical M. tuberculosis isolates in multiple studies [83][84][85][87][88][89][90][91][92][93][94][95][96][97]. The presence of S95 or T95 at gyrA codon 95 is a naturally occurring polymorphism that is not associated with resistance of M. tuberculosis isolates to FQs.…”
Section: Mechanism Of Action and Resistance Of Fluoroquinolones In Mmentioning
confidence: 99%
See 1 more Smart Citation
“…In (Jacobs 1999;Piddock 1999;Bryskier and Lowther 2002;Victor, van Helden et al 2002;Jacobs 2004) (Takiff, Salazar et al 1994;Cambau, Sougakoff et al 1994 (2); Alangaden, Manavathu et al 1995;Sullivan, Kreiswirth et al 1995;Kocagoz, Hackbarth et al 1996;Takiff, Cimino et al 1996;Williams, Chan et al 1996;Xu, Kreiswirth et al 1996;Perlman, El Sadr et al 1997;Sougakoff, Lemaitre et al 1997;Zhou, Dong et al 2000;Lee, Tang et al 2002;Siddiqi, Shamim et al 2002;Yew, Chan et al 2002;Johansen, Larsen et al 2003;Cheng, Yew et al 2004;Post, Willcox et al 2004;Giannoni, Iona et al 2005) (Ginsburg, Grosset et al 2003;Wade and Zhang 2004) …”
Section: Zusammenfassungmentioning
confidence: 99%
“…Other molecular assays that have been developed for the detection of resistance markers have included locked nucleic acid probes (van Doorn et al, 2008) and multiplex PCR amplimer conformation analysis (Cheng et al, 2004), pyrosequencing (Marttila et al, 2009;Garza-Gonzalez et al, 2010;Halse et al, 2010), oligonucleotide microarray (Caoili et al, 2006), and mass spectrometry (Wang et al, 2011).…”
Section: Molecular Detection Of Resistance Markersmentioning
confidence: 99%